A Study on Green Advertising Effectiveness in the Perspective of Image Proximity - Sheng, Guanghua; Xia, Qing; Yue, Beibei; Li, Yuqi (Frontiers in Psychology, 2021)
Based on the construal level theory (CLT), this study discusses the effects of congruence between image proximity and product type on advertising attitude and product attitude from the perspective of spatial distance and investigates the mediating role of mental imagery. Data are collected using two laboratory experiments and one online experiment. A two-way ANOVA is used to test the interaction between image proximity and product type, and a bootstrap analysis is used to test the mediating role of mental imagery. The result shows that: (1) For search products, compared with full-length shots, the close-up shots of environmental information can enable consumers to generate more positive advertising attitude and product attitude. For experience products, the full-length shots of environmental information can enable consumers to generate more positive advertising attitude and product attitude than the close-up shots. (2) The congruence effect of image proximity and product type has an impact on advertising attitude and product attitude through mental imagery. This research uses different kinds of image proximity to express environmental information about green products and tries to interpret the effectiveness of green advertisements from a new perspective.